ANALISIS YURIDIS TERHADAP PEMENUHAN HAK ISTRI DAN ANAK PASCA PERCERAIAN: STUDI PUTUSAN PENGADILAN AGAMA SUKOHARJO NOMOR 573/PDT.G/2024/PA.SKH - Arkan, Miftahul; Muhammad Kurniawan Budi Wibowo; Aditya Fajri Kurnia Pradana (LPPM STAI Muhammadiyah Probolinggo, 2025)
Divorce not only ends the marriage bond, but also has significant legal consequences, especially regarding the fulfilment of the rights of women and children. Problems that often arise include the provision of maintenance, housing, mut'ah, and child custody (hadhanah) after divorce. This study aims to analyse the fulfilment of the rights of wives and children based on Sukoharjo Religious Court Decision Number 573/Pdt.G/2024/PA.Skh, by reviewing the extent to which the considerations and rulings of the decision are in line with Islamic law and Indonesian positive law. This research uses a normative juridical method with a case study approach. Data were obtained through reviewing the decision documents and analysed using the theory of distributive justice and maqashid sharia. The results showed that there was still a discrepancy between what the judge decided and its implementation in the field, especially in terms of providing maintenance and executing children's rights. In addition, it was found that the legal considerations in the decision did not fully reflect the principle of protection of vulnerable parties as mandated in maqashid sharia. Therefore, this study recommends the need for reformulation of the judges' consideration approach in divorce cases as well as strengthening the implementing regulations to ensure the effectiveness of post-divorce rights fulfilment.